After putting the value of y from the second equation to the first equation, the resultant equation is [tex]x=5[/tex].
GIven:
The equations are:
[tex]3x + y = 1\\ y = 6 - 4x[/tex]
It is required to put the value of y from second equation to the first equation.
The value of y from the second equation is,
[tex] y = 6 - 4x[/tex]
Now, put this value of y in the first equation as,
[tex]3x + y = 1\\ 3x+(6 - 4x)=1\\ 3x+6-4x=1\\ -x=-5\\ x=5[/tex]
Therefore, after putting the value of y from the second equation to the first equation, the resultant equation is [tex]x=5[/tex].
For more details about equations, refer to the link:
https://brainly.com/question/2263981